Public Procurement of Energy Efficient Products Lessons from Around the World - Singh, Jas; Culver, Alicia; Bitlis, Melis (World Bank, Washington, DC, 2014)
This report assesses global experiences with Energy Efficient Purchasing (EEP) as a tool to help governments improve the efficiency of their facilities and public services. In many developed countries, EEP is increasingly becoming subsumed within broader Green Public Procurement (GPP) or sustainable procurement policies, where EE is only one indicator among many others. Global energy needs are increasing at a steady pace. Rapid industrial development and growing populations have led to an exponential growth in worldwide energy consumption. According to the international energy agency, demand for energy is projected to grow steadily from 2010 to 2035, representing a 40 percent increase. About 90 percent of this increase will come from developing countries. As these countries continue to urbanize, develop their industrial infrastructure, and provide universal access to basic services, strains on the existing energy infrastructure and resources will intensify. This, coupled with a substantial rise in the middle class in many of the emerging economies, most notably China and India, will also contribute to this increase in demand. This contributes to the expected rise in non-OECD (Organization of Economic Cooperation and Development) countries' share of global energy demand, from 54 percent in 2009 to 64 percent by 2035. This projected increase in energy demand will necessitate new solutions to help bridge the gap between supply and demand, while reducing the trillions of dollars required for new energy infrastructure investments. The study concluded that EEP policies and programs can be an effective way to promote energy efficient products by leveraging a government's purchasing power and influence. Countries with more advanced programs have a wealth of resources and experiences available for countries just getting started, which can dramatically lower the time and resources needed to launch such efforts. As countries improve enforcement and tracking efforts, enhanced methods will be developed and tested, providing models for adaptation and application in the developing world.